Interactive E-Module Based on Contextual Teaching and Learning as a Digital Learning Media for Elementary School Students - Oka Cahya Ningrum; Anak Agung Gede Agung; Ida Bagus Gede Surya Abadi (International Journal of Elementary Education, 2026)
The limited use of interactive digital learning materials, along with low student motivation and conceptual understanding, remains a major challenge in Natural and Social Sciences (IPAS) learning, particularly on the topic of states and changes of matter in elementary education. Learning processes that are insufficiently contextual and fail to connect content with students’ real-life experiences result in less meaningful learning. This study aims to develop, evaluate the feasibility, and examine the effectiveness of an interactive e-module based on Contextual Teaching and Learning (CTL) as a learning medium for IPAS. This study employed a Research and Development approach using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. The research subjects were second-grade elementary school students. Data were collected through questionnaires and learning outcome tests, using expert validation sheets and test instruments. Data analysis was conducted using descriptive quantitative techniques and inferential statistics through a t-test. The results indicate that the CTL-based interactive e-module is highly feasible based on expert validation and effective in improving students’ learning outcomes. In addition, the use of the e-module contributes to increased learning motivation, student engagement, and conceptual understanding. These findings imply that CTL-based interactive e-modules can serve as an innovative and contextual learning medium to support IPAS instruction in elementary schools.